Design of a new haptic device and experiments in minimally invasive surgical robot. (31st October 2017) - Wang, Tao; Pan, Bo; Fu, Yili; Wang, Shuguo; Ai, Yue
Abstract: In this paper, we designed a 8 degrees of freedom (DOFs) haptic device for applications in minimally invasive surgical robot. The device can provide three translational, three rotational and a grasping motion and force feedback capability. It is composed of three parts, including an arm mechanism, a redundant wrist mechanism and a grasper mechanism. The kinematics and gravity compensation algorithms are also detailed in the paper. In addition, the haptic device and a slave surgical robot for minimally invasive surgery (MIS) developed by our lab are integrated as a master-slave surgical robotic system in this paper. In the master-slave robotic system, a new control system is designed to realize real-time mater-slave control based on EtherCAT bus technology. Experiments show that the haptic device can effectively compensate gravity at any position in its workspace and successfully realize master-slave operation by the control method, which prove the haptic device designed in this paper can be used as a master manipulator to control the surgical robot.